1994
DOI: 10.1128/iai.62.3.769-778.1994
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-inhibitable lectin activity of the filamentous hemagglutinin adhesin of Bordetella pertussis

Abstract: Bordetella pertussis, the etiologic agent of whooping cough, produces an outer membrane-associated filamentous hemagglutinin (FHA) which is the major adhesin of this organism. FHA exhibits a lectin-like activity for heparin and dextran sulfate. By using in vitro adherence assays to cultured epithelial cells, the attachment of B. pertussis was reduced in the presence of sulfated polysaccharides such as heparin and dextran sulfate but not in the presence of dextran, indicating the crucial role of polysaccharide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(72 citation statements)
references
References 55 publications
3
68
0
Order By: Relevance
“…Mice were exposed to live virulent or attenuated bacteria, and sensitized to allergen during infection. Virulent B. pertussis BPSM [20] and attenuated BPZE1 were cultured as previously described [21]. Attenuated or virulent strains at mid-log growth were administered to mice by aerosol using the respiratory challenge model and standard protocols [16].…”
Section: Methodsmentioning
confidence: 99%
“…Mice were exposed to live virulent or attenuated bacteria, and sensitized to allergen during infection. Virulent B. pertussis BPSM [20] and attenuated BPZE1 were cultured as previously described [21]. Attenuated or virulent strains at mid-log growth were administered to mice by aerosol using the respiratory challenge model and standard protocols [16].…”
Section: Methodsmentioning
confidence: 99%
“…The presence of an N-terminal carbohydrate binding domain, and the co-regulation of cdrAB with the pel and psl gene clusters led us to propose that CdrA may bind to one of these polysaccharides. There is precedence for sugar binding in this particular family of adhesins (Menozzi et al, 1994b). Like CdrA, expression of FHA of B. pertussis induces liquid culture auto-aggregation.…”
Section: Cdrab-mediated Auto-aggregation Requires the Psl Polysaccharidementioning
confidence: 99%
“…Previous models for TPS show the TpsA N-terminus emerging first from the outer membrane channel (Henderson et al, 2004;Jacob-Dubuisson et al, 2004;Thanassi et al, 2005) and the N-terminus of FHA has been shown to be involved in carbohydrate-dependent haemagglutination in vitro, suggesting a role in adherence (Sandros and Tuomanen, 1993). A heparin binding domain located near the FHA N-terminus has also been implicated in epithelial cell binding (Menozzi et al, 1994). Although most anti-FHA antibodies generated in response to infection by B. pertussis are directed against the C-terminus (Leininger et al, 1997), this region of the protein was not previously thought to represent a functional domain.…”
Section: The C-terminus Of Fhab Is Required For Fha Function In Vivomentioning
confidence: 99%